Optimization of Humic Acid and Vermicompost on the Growth and Yield of Soybean (Glycine max (L.) Merrill) - Marom, Siwi Lutfi Nailul; Ilham Muhklisin; Christa Dyah Utami; Tirto Wahyu Widodo (International Integrated Agricultural Journal (IIAJ), 2026)
National soybean productivity tends to decline each year due to land degradation caused by excessive use of synthetic fertilizers. This dependence can be reduced by applying humic acid and vermicompost. This research aims to examine the effect of humic acid and vermicompost on soybean growth and yield. The research was conducted from August to November 2024 at the Jember State Polytechnic research site, using a factorial Randomized Block Design (RAK) with two factors and three replications. The first factor is the dosage of humic acid (10, 20, 25, and 30 kg/ha), and the second factor is the dosage of vermicompost (15 and 20 tons/ha). Data were analyzed using ANOVA, followed by the DMRT test at a 5% or 1% level. The research results showed that the combination of 25 kg/ha humic acid and 20 tons/ha vermicompost significantly affected the number of root nodules (7.17 pieces). Separately, the application of 20 kg/ha humic acid significantly affected the fresh pod weight per sample (2.02 g) and the fresh pod weight per plot (124.89 g). Vermicompost at 20 tons/ha also had a significant effect on plant height (26.69 cm). These findings indicate that humic acid and vermicompost have the potential to improve soil fertility and nutrient availability for soybean plants.